Strategies to identify individuals with monogenic diabetes: results of an economic evaluation. Issue 3 (18th March 2020) - Peters, Jaime L; Anderson, Rob; Shields, Beverley; King, Sophie; Hudson, Michelle; Shepherd, Maggie; McDonald, Timothy James; Pearson, Ewan; Hattersley, Andrew; Hyde, Chris
Abstract : Objectives: To evaluate and compare the lifetime costs associated with strategies to identify individuals with monogenic diabetes and change their treatment to more appropriate therapy. Design: A decision analytical model from the perspective of the National Health Service (NHS) in England and Wales was developed and analysed. The model was informed by the literature, routinely collected data and a clinical study conducted in parallel with the modelling. Setting: Secondary care in the UK. Participants: Simulations based on characteristics of patients diagnosed with diabetes <30 years old. Interventions: Four test-treatment strategies to identify individuals with monogenic diabetes in a prevalent cohort of diabetics diagnosed under the age of 30 years were modelled: clinician-based genetic test referral, targeted genetic testing based on clinical prediction models, targeted genetic testing based on biomarkers, and blanket genetic testing. The results of the test-treatment strategies were compared with a strategy of no genetic testing. Primary and secondary outcome measures: Discounted lifetime costs, proportion of cases of monogenic diabetes identified. Results: Based on current evidence, strategies using clinical characteristics or biomarkers were estimated to save approximately £100–£200 per person with diabetes over a lifetime compared with no testing. Sensitivity analyses indicated that the prevalence of monogenic diabetes, the uptake of testing, and the frequency of home blood glucose monitoring had the largest impact on the results (ranging from savings of £400–£50 per person), but did not change the overall findings. The model is limited by many model inputs being based on very few individuals, and some long-term data informed by clinical opinion. Conclusions: Costs to the NHS could be saved with targeted genetic testing based on clinical characteristics or biomarkers. More research should focus on the economic case for the use of such strategies closer to the time of diabetes diagnosis. Trial registration number: NCT01238380 .